The little house of hope - Jennings, Terry Catasús (Neal Porter Books, Holiday House, 2022)
"When Esperanza and her family arrive in the United States from Cuba, they buy a little house, una casita. It may be small, but they soon prove that there's room enough to share with a whole community"--